2001
DOI: 10.1021/ja010079n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Histidine Deligation from the Heme in GuHCl-Unfolded Fe(III) Cytochrome c Studied by a Laser-Induced pH-Jump Technique

Abstract: We have developed an instrumental setup that uses transient absorption to monitor protein folding/unfolding processes following a laser-induced, ultrafast release of protons from o-nitrobenzaldehyde. The resulting increase in [H(+)], which can be more than 100 microM, is complete within a few nanoseconds. The increase in [H(+)] lowers the pH of the solution from neutrality to approximately 4 at the highest laser pulse energy used. Protein structural rearrangements can be followed by transient absorption, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…The photoexcitation of an aqueous solution of 2-NBA with a 355 nm nanosecond laser pulse leads to the release of protons in high yield (Φ H + ) 0.45) within a few nanoseconds (25,(27)(28)(29). The concentration of photoreleased protons can reach the range of 10 -4 M with laser pulses of a few tens of mJ (30,31). At low laser pulse energies, the concentration of photoreleased protons is proportional to the laser pulse energy.…”
Section: Methodsmentioning
confidence: 99%
“…The photoexcitation of an aqueous solution of 2-NBA with a 355 nm nanosecond laser pulse leads to the release of protons in high yield (Φ H + ) 0.45) within a few nanoseconds (25,(27)(28)(29). The concentration of photoreleased protons can reach the range of 10 -4 M with laser pulses of a few tens of mJ (30,31). At low laser pulse energies, the concentration of photoreleased protons is proportional to the laser pulse energy.…”
Section: Methodsmentioning
confidence: 99%
“…This proton releasing reaction was applied to the pH change of a solution containing Mb and Cyt c to monitor the protein unfolding dynamics of Mb and Cyt c by the PA method and transient absorption method, respectively. 3,8 To study the NBA reaction with the presence of a protein, we investigated the TG signal with Mb in NBA aqueous solution. We found that the TG signal changed dramatically by adding the protein as shown in Figure 4.…”
Section: Electrolytementioning
confidence: 99%
“…3,8 Protein folding of apomyoglobin (Mb) 3 and cytochrome c (Cyt c) 8 were studied by the photoactoustic (PA) method and transient absorption method, respectively. However, in their analyses, the photochemical reaction of NBA is assumed to be the same as that in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced pH jumps use the application of a laser pulse to induce proton transfer to or from a small molecule included in the reaction buffer. The proton transfer kinetics are extremely fast; the time resolution of a few nanoseconds is determined by shape of the pump laser pulse (Abbruzzetti et al ., 2001a; Abbruzzetti et al ., 2001b). As might be expected, pH jumps have been applied primarily to heme binding proteins (e.g.…”
Section: Learning From Simulation and Experimentsmentioning
confidence: 99%